Enhancing solid fuel potential of water hyacinth: A study on chemical modification through composting and demineralization - Mustagfirin, Mustagfirin; Hermawan, Dede; Nawawi, Deded Sarip; Kusumah, Sukma Surya; Ismayati, Maya; Sutiawan, Jajang; Ningrum, Riska Surya; Wikantyoso, Bramantyo (Center of Biomass & Renewable Energy (CBIORE), 2026)
Rapid growth makes water hyacinth (WH) an exceptional biomass resource, but its low calorific value and elevated ash content hinder its application as a sustainable green energy source. This study aims to enhance the quality of water hyacinth as a solid fuel by increasing lignin content through composting and decreasing ash content by demineralization. The composting period for water hyacinth was modified to 4, 7, 11, and 15 days, followed by a demineralization process employing two solvents: water and 5% nitric acid (HNO₃). Proximate, ultimate, and chemical studies were conducted on water hyacinth before and following treatment to ascertain its specific alterations. This study indicates that after 15 days of composting, the lignin fraction increased from 10.01% to 15.14%. Demineralization employing a combination of water and nitric acid can substantially reduce ash content (19.4%). The demineralization of raw materials during composting is more efficacious in diminishing ash content than the demineralization of raw materials before composting. The most significant reduction was 46.17%, observed in the 11-day WH composting, where the ash content decreased from 22% to 11.84%. According to the results, modified WH is a viable raw material for solid fuel due to its enhanced lignin content and reduced ash level.